Simulation Study on the Evolutionary Game Mechanism of Collaborative Innovation in Supply Chain Enterprises and Its Influencing Elements - Jue-Ping Xie; Huai-Ying Lei (Journal of Mathematics)
Collaborative innovation between companies is critical for increasing supply chain value. However, as a dynamic game process, the collaboration between manufacturer, provider, and seller in the supply chain is influenced by a range of elements. This paper is set out to investigate the collaborative innovation strategy adopted by manufacturer, supplier, and distributor (the “three players”). To meet this end, an analytical framework was built to study the evolutionary game of collaborative innovation in supply chain enterprises. Based on the analysis, this research further studied the dynamic evolutionary mechanism and influencing elements through four different simulation cases. The research showed the following. (1) When the three players have equal innovative capability, they are more willing to contribute to innovation if the projected revenue is higher reflecting an increasing coefficient of collaborative innovation gains. As a result, the three players are more likely to agree on their cooperation approach. (2) When the three players have different independent and innovative capabilities, they are more willing to innovate if the collaborative innovation gain coefficient increases, but supply chain players with stronger capability are more active to innovate than their peers. In other words, strong innovators attach particular attention to innovation. (3) When any collaborative innovation could generate profits for all players in the supply chain, the player who enjoys the benefit but lacks innovative capability will be unwilling to cooperate with others if additional gains rise. Thus, better maintenance of the stability of the collaborative innovation system requires a strictly implemented coordination mechanism.